KUALITAS PRODUK CASCARA CELUP DENGAN PENAMBAHAN JAHE MERAH (Zingiber officinale var. Rubrum): Product Quality of Cascara Infusion with the Addition of Red Ginger (Zingiber officinale var. Rubrum) - Indah Nalurita; Sony Suwasono; Nita Kuswardhani; Fuad Sauqi Isnain (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2023)
Cascara is a herbal beverage product derived from processed coffee skin waste. However, the acidic odor of cascara is not favored by consumers. To improve the quality of cascara, is to combine them with red ginger (Zingiber officinale var. Rubrum). Red ginger contains volatile components such as zingiberene and zingiberol, which provide a distinctive fresh aroma that can mask the sour odor of cascara. The purpose of this study was to determine the effect of different ratios of cascara and red ginger on the physical, chemical, organoleptic, and microbiological quality of tea bags containing cascara with added red ginger, in order to obtain the best formulation. This research was conducted using a randomized complete block design (RCBD) with four treatment ratios: T0 (100% cascara: 0% red ginger), T1 (90% cascara: 10% red ginger), T2 (80% cascara: 20% red ginger), T3 (70% cascara: 30% red ginger), and T4 (60% cascara: 40% red ginger). The different ratios of cascara and red ginger significantly influenced the physical, chemical, organoleptic, and microbiological properties of the tea bags containing cascara with added red ginger. The best formulation was obtained from treatment T3 (70% cascara: 30% red ginger), which had a color preference rating of 4.15, an aroma preference rating of 4.34, a taste preference rating of 4.17, an L* value of 32.377, a pH value of 5.05, a moisture content of 13.461%, a total phenol content of 21.105 mg GAE/g, an antioxidant activity of 68.115%, and a total microbe count of 3.36 × 103 CFU/ml.